1990
DOI: 10.1095/biolreprod43.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Proportion of Type I and Type III Collagen in the Developing and Retained Bovine Placentome

Abstract: The proportions of Type I and Type III collagen were evaluated from gestational, postpartum-retained, and released bovine placental membranes. Placentomes were excised at 90, 150, 210, and 270 days of gestation (n = 32) and from postpartum-retained (2 and 12 h, n = 8) and released (2 h, n = 4) membranes. Placentome components were processed for collagen, hydroxyproline, protein, and dry weight determination. Collagen extracts were separated by SDS-PAGE. Densitometry was used to establish the proportions of col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 30 publications
0
14
0
2
Order By: Relevance
“…In the bovine estrous cycle, fibronectin was distributed diffusely throughout the endometrial tissue, and integrin β1 subunit was present in the endometrial stroma [17]. The bovine placentome is composed of an interdigitation of cotyledonary and caruncular villi, and the rich vascular system and the majority of types I and III collagens are localized within the maternal villi [25]. The present study demonstrated that there was a parallel decrease in the expression of type I collagen and fibronectin during the early implantation period and that the feature of collagen fibers remarkably changed from thick and dense to thin and rough.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the bovine estrous cycle, fibronectin was distributed diffusely throughout the endometrial tissue, and integrin β1 subunit was present in the endometrial stroma [17]. The bovine placentome is composed of an interdigitation of cotyledonary and caruncular villi, and the rich vascular system and the majority of types I and III collagens are localized within the maternal villi [25]. The present study demonstrated that there was a parallel decrease in the expression of type I collagen and fibronectin during the early implantation period and that the feature of collagen fibers remarkably changed from thick and dense to thin and rough.…”
Section: Discussionmentioning
confidence: 99%
“…The type IV collagen and laminin constitute customarily the basement membrane of epithelium, blood vascular vessels and various kinds of gland [5,25]. The structure of type IV collagen is expressed as a network of mesh sheets and serves as multiple cell-binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Se o sistema de ancoragem não é enzimaticamente degradado, as membranas fetais ficam retidas. Vacas com RP apresentam uma colagenólise diminuída (Gross et al 1985, Melendez et al 2006, ou ainda um sistema anti-colagenase mais ativo (Eiler & Hopkins 1993), sendo incapazes de degradar o colagénio tipo III, que diminui significativamente em vacas normais no final da gestação (Sharpe et al 1990).…”
Section: Discussionunclassified
“…Microscopicamente, a grade contendo 25 pontos equidistantes foi sobreposta a 80 campos microscópicos escolhidos aleatoriamente, totalizando 2000 pontos por lâmina. O número de vezes em que os pontos atingiram uma determinada estrutura foi utilizado para calcular a proporção volumétrica dela, segundo a fórmula de Sharpe et al (1989).…”
Section: Methodsunclassified